2018
DOI: 10.1002/hed.25601
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1 and PD‐L1 in locoregionally advanced nasopharyngeal carcinoma: Substudy of a randomized phase III trial

Abstract: Background To evaluate the expression of programmed death‐1 (PD‐1) and programmed death‐ligand 1 (PD‐L1) by using immunohistochemistry analysis in locoregionally advanced nasopharyngeal carcinoma (NPC) patients receiving cisplatin, fluorouracil, and docetaxel followed by concurrent chemoradiotherapy. Methods As part of a previously reported trial, 108 patients were enrolled in this study. Results We observed that Epstein–Barr Virus (EBV) antibody levels were associated with PD‐1 positive staining in NPC and PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Among all the original reports eligible in our study, some of the studies demonstrated that relatively higher expression of PD-L1 or PD-1 in NPC predicts worse prognosis [22, 24, 26, 28, 29, 31, 3436]. The most common and convincing explanation for the result was the interactions of PD-1 and PD-L1 would lead to immune suppression and promote tumor progression [38, 40].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Among all the original reports eligible in our study, some of the studies demonstrated that relatively higher expression of PD-L1 or PD-1 in NPC predicts worse prognosis [22, 24, 26, 28, 29, 31, 3436]. The most common and convincing explanation for the result was the interactions of PD-1 and PD-L1 would lead to immune suppression and promote tumor progression [38, 40].…”
Section: Discussionmentioning
confidence: 90%
“…A total of 1836 patients from 15 included studies concerning PD-L1 [1517, 2233] and 678 patients from six studies regarding PD-1 [22, 30, 31, 3436] were included in the meta-analysis. The publication year of PD-L1 and PD-1 ranged from 2014 to 2018 and 2010 to 2018, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, the full text of 16 studies was assessed; five studies were excluded because of insufficient data ( n = 2), duplicate studies from the same research group ( n = 2), and no use of IHC ( n = 1). Finally, 11 studies were included in this meta-analysis (1823, 26, 27, 3133).…”
Section: Resultsmentioning
confidence: 99%
“…Using immunohistochemistry (IHC), PD-L1 overexpression was shown to be associated with a poor prognosis across multiple tumor types (10, 13), including non-small cell lung cancer (14), hepatocellular carcinoma (15), colorectal cancer (16), and renal cell carcinoma (17). Several studies also demonstrated the relationship between PD-L1 expression and prognosis of patients with NPC; however, results were controversial (1823). Therefore, we conducted a meta-analysis to assess the impact of PD-L1 on the prognosis of patients with NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven studies published from 2014 to 2018 were included in the meta-analysis (Table I). 4,[9][10][11][12][13][14][15][16][17][18] The total number of participants was 1,356; sample sizes ranged from 56 to 209. Most studies were retrospective (10/11).…”
Section: Study Characteristicsmentioning
confidence: 99%